EFFECT OF NAOH CONCENTRATION AND RESIDENCE TIME ON THE CONVERSION OF REMOVAL OF Ca2+ AND Mg2+ IN SEAWATER CONTINUOUSLY USING AN BAFFLED REACTOR - Dita Nurmala Tristanti; Harishul Ulum; Soemargono Soemargono; Nove Kartika Erliyanti (Konversi, 2021)
The aims of this study were to determine the effect NaOH concentration and residence time on the conversion of calcium (Ca2+) and magnesium (Mg2+) removal as impurities. The concentration of NaOH used in this study were 0.05N, 0,1N, 0.15N, and 0,2N. The reactor used in this study is an baffled reactor equipped with air as a stirrer with air flow rates of 10000, 15000, 20000, 25000, and 30000 ml/minute. The ratio between the flow rate of seawater toward the flow rate of NaOH solution in this study was 85ml/minute : 25ml/minute.The results showed that the NaOH concentration and residence time had a significant effect on the conversion of removal of (Ca2+) and magnesium (Mg2+) impurities. The best results were obtained at 0.25N NaOH concentration, residence time of 13,08 minute, and gas flow rate of 30000ml/minute with removal conversion of calcium (Ca2+) of 73.083% and magnesium (Mg2+) of 89.621%.